Tinjauan Yuridis Terhadap Penanaman Ganja Di Kawasan Konservasi Bromo (Kajian Undang-Undang Lingkungan Hidup & Hukum Pidana) - Zai, Vingi Julisman; Ramadhana, Widodo (Universitas Muhammadiyah Kotabumi, 2025)
This study examines the enforcement of laws against the illegal cultivation of cannabis within the conservation area of Bromo Tengger Semeru National Park (TNBTS), viewed through the lens of Law No. 32 of 2009 on Environmental Protection and Management, and Law No. 35 of 2009 on Narcotics. Despite TNBTS being a highly protected area, 59 cannabis plots were discovered in its wilderness zone, resulting in significant ecological damage, including disruption of endemic plant habitats. This illegal cultivation constitutes dual violations: a narcotics crime and environmental destruction, both carrying severe criminal penalties. The findings highlight weak supervision by TNBTS management and insufficient legal outreach to local communities as contributing factors. Meanwhile, efforts to restore the ecosystem face challenges related to funding and inter-agency coordination. Employing a normative juridical approach, this study emphasizes the importance of collaboration among law enforcement, conservation authorities, and public education in preventing similar crimes and ensuring environmental sustainability